Collins, Blanche (audio interview #1 of 2) - Collins, Blanche (1904 - 10/4/1983); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This is the first of two interviews conducted in Collins' condo near Belmont Shore; the interviewer could look out the window and see sailboats. The interviewer grew up in Long Beach during the fight that Collins led against censorship of the Long Beach Public Library. 8/1/1979